Physical and mechanical properties of titanium alloy VT1-0 after high-current electron beam irradiation - Klepikov, V.F.; Lonin, Yu.F.; Ponomarev, A.G.; Startsev, O.A.; Uvarov, V.T. (Вопросы атомной науки и техники, 2015)
Titanium alloy VT1-0 was modified by the high-current electron beam irradiation with energy 0.35 MeV, 5 μs impulse, and power density of 60 MW⋅cm-2. It was found that intense electron exposure significantly increased both hardness (by 30%) and elastic modulus (by 12%) within a subsurface layer of 100 μm thick. The thermoelastic model of the metal ablation was developed. Description of dynamics of the induced temperature and deformations distributions has been performed using the finite difference and finite element methods.